A CONCEPTUAL APPRAISAL OF VIRECHANA KARMA (AYUSHDHARA, 2018)
Panchakarma is getting global attention nowadays and Virechana is one among its procedures which is actively used by the Ayurvedic fraternity. Four different types of Virechana namely Anulomana, Sramsana, Bhedana and Rechana are mentioned in our classics but they are not apprised properly for their clinical utility. The Brihattrayis give ample illustrations of their use without highlighting the underlying rationale. Sarangdhara Samhita defines each of this therapeutics without indicating the disease conditions. This paper tries to understand the specific clinical utility of the four types of Rechana by tracing back their indications in scriptures. Anulomana is a mild form of Virechana where the Paka of Malas occur. Sramsana is a mild form of Virechana which does not cause Paka of Malas. Bhedana does not cause Paka of Malas but it is a strong type of Virechana. Rechana also does not cause Paka of mala but the strength of the procedure can be modulated by the use of different types of drugs. The selection of the type of Rechana depends on the pharmaco-therapeutic action necessary to harmonise the Dosa, Dhatu and Mala without causing any further complication or Upadrava.